Examination of the twinning activity in additively manufactured Ti-6Al-4V. (15th April 2018) - Zhong, H.Z.; Zhang, X.Y.; Wang, S.X.; Gu, J.F.
Highlights: {10-11} twins with small stress and strain are preferred in additively manufactured Ti-6Al-4V. {10-11} twins play threes effects of accommodating shape strain, assisting sheas strain and acting as LIS. The secondary twinning forms in the latter thermal cycles with small driving force to promote martensite transformation. Graphical abstract: Abstract: This present paper investigates the dominant twinning mode and secondary twin via transmission electron microscopy at different positions of additively manufactured (AM) Ti-6Al-4V deposition wall fabricated by laser metal deposition (LMD). {10−11} 〈−1012〉 twinning system is observed as the dominant twinning mode. Secondary twins, including the inserting secondary twin and neighboring secondary twin, are characterized at position with sufficient thermal cycle history. These twinning morphologies can be rationalized to some degree from the standpoint of the twinning effect and thermal condition in additive manufacturing. This work gets insight into the twinning evolution in additively manufactured Ti alloys.